Visualization and evaluation of concrete damage in-service headworks by X-ray CT and non-destructive inspection methods - Morozova, Nadezhda; Shibano, Kazuma; Shimamoto, Yuma; Tayfur, Sena; Alver, Ninel; Suzuki, Tetsuya (Frontiers in Built Environment, 2022)
The durability of concrete irrigation infrastructures decreases easily due to environmental effects, such as the freeze-thawed process. The degree of damage in concrete is, in most cases, evaluated by an unconfined compression test or ultrasonic test. The limiting states of structures are the result of a gradual accumulation of microdefects during the in-service period, which leads to the initiation and development of macroscopic cracks, loss of performance and destruction. Therefore, to maintain such structures, it is necessary to properly determine the degree of damage by non-destructive testing. For effective maintenance and management of in-service structures, it is necessary to evaluate not only such mechanical properties as strength but also the degree of damage. Quantitative damage evaluation of concrete is proposed by applying the X-ray CT method and related non-destructive inspection, which is based on estimating cracking damage effects. In this study, the damage evaluation of concrete-core samples is investigated by X-ray CT parameters and the non-destructive parameters. The tested samples were taken from the damaged concrete headworks, which was constructed after about 50 years in Niigata, Japan.